STORYTELLING METHOD USING HAND PUPPET MEDIA: COGNITIVE DEVELOPMENT OF CHILDREN AGED 4-6 YEARS - Sumartiningsih Indah (Journal of Education Technology and Inovation, 2024)
The main purpose of the study on storytelling methods with hand puppet media in relation to the cognitive development of children aged 4-6 years is to understand and analyze the impact of using hand puppets as an aid in storytelling activities on various aspects of cognitive abilities in preschool children and to explore how children's interactions with hand puppets in the context of stories can improve language skills, conceptual understanding, information processing, logical thinking skills, problem-solving skills, emotional intelligence, and literacy basics. This study uses a quantitative quasi-experimental design approach. The subjects of the study were 19 students aged 4-6 years at Labscool Kindergarten in the form of one group pretest-posttest design analyzed using the Paired Samples Test. The results of the Paired Samples Test data analysis, it can be concluded that there is a significant difference between the pre-test and post-test scores. showing an average decrease of 8,474 points in the cognitive development of children aged 4-6 years. Because the p value is very small (0.000), this difference is very statistically significant. This means that there is a clear impact of using this method in improving children's cognitive development. cognitive enhancement in children through storytelling methods with hand puppet media in accordance with existing theories regarding cognitive stimulation at an early age. This method is very effective in improving various aspects of child development, especially in terms of thinking skills, speaking skills, and their understanding of the social world around them